2003
DOI: 10.2307/3583344
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Knowledge, Sexual Behaviour and Contraceptive Use among Adolescents in Niger State of Nigeria

Abstract: Code Number: rh03007 ABSTRACT Eight hundred and ninety six adolescents aged 11-25 years were recruited into this study using a multi-stage random sampling method. Overall, about 33% of them had already had first sexual experience but more males than females reported having experienced first sexual encounter. Only 3.6% of the respondents were married. One half of the sexually experienced adolescents had more than one sexual partner at the time of the study. Majority of the respondents (91.9%) had heard about HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
(15 reference statements)
6
24
1
Order By: Relevance
“…Awareness about HIV/AIDS in the population was almost universal. This has been reported in other studies [10,11,12,13]. The Nigerian Demographic and Health Survey carried out in 2003 [14] showed that 97% of men had ever heard of AIDS and as in this study there was little variation by socio-demographic variables.…”
Section: Discussionsupporting
confidence: 84%
“…Awareness about HIV/AIDS in the population was almost universal. This has been reported in other studies [10,11,12,13]. The Nigerian Demographic and Health Survey carried out in 2003 [14] showed that 97% of men had ever heard of AIDS and as in this study there was little variation by socio-demographic variables.…”
Section: Discussionsupporting
confidence: 84%
“…There is a general decline in the age of sexual debut, as is found in other parts of the world. [24][25][26] This may be related mainly to a loss of family values and cultural values. The mass media have also influenced youths negatively, and a study found that adolescents whose older siblings had indulged in premarital sex were likely to follow suit.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, the gender structure and asymmetries depicted above are influenced and nurtured by customs, cultures, and traditions, which are difficult to change (Nwankwo 2001;Sunmola et al 2003). The inference drawn from these essentialist gender perspectives is that women in sub-Saharan Africa imbibe the putatively static customs, cultures, and traditions that make them vulnerable to STIs and other patterned asymmetries without penetration, contestation, and agency.…”
Section: Introductionmentioning
confidence: 99%